FENOMENA OVERSHARING DI INSTAGRAM PADA GENERASI MUDA DI KOTA TANJUNG PINANG - Sigalingging, Novrianti Frederika; Elsera, Marisa; Syafitri, Rahma (Master Program in Sociology, Faculty of Social and Political Sciences, Universitas Sriwijay, 2023)
The use of social media for the majority of the younger generation is in the stage of adjusting to society's life. When using a smartphone and connected to the internet, social media users can freely interact without being hindered by time and place. This causes oversharing in the younger generation, oversharing, namely individual behavior that is excessive in sharing something on their social media accounts, with this oversharing the young generation in Tanjungpinang City has a pattern in uploading photos or videos on Instagram accounts. Researchers used a type of qualitative research method, with the technique of determining the informant, namely purposive sampling technique. Researchers took as many as 6 informants. With data collection techniques using observation, interviews, and documentation as well as data analysis techniques in this study using concepts related to symbols, existence and taste. The results of this study show that there are young people in Tanjungpinang City who upload photos or videos through symbols and display activities that show the existence and tastes of the account owner.